Smart Diary Forms: Artificial Intelligence for Efficient Diary Farming - Delshi Howsalya Devi Ramamoorthy; Divakara Baburayanakoppal Chandrashekhar; Tilak Kumar Lakshmanaswamy; Shilpa Krishne Gowda; Kumutha Duraisamy; Sundresan Perumal (International Information and Engineering Technology Association, 2026)
Indexed by Scopus